Effect of dandelion leaves and fenugreek seeds with or without enzyme addition on performance and blood biochemistry of broiler chicken, and evaluation of their in vitro antibacterial activity - QURESHI, SAIM; BANDAY, M T; ADIL, SHEIKH; SHAKEEL, IRFAN; MUNSHI, Z H (The Indian Journal of Animal Sciences, 2015)
The study was conducted to evaluate effect of dietary supplementation of locally available herbs dandelion leaves and fenugreek seeds with or without enzyme treatment in broiler chicken. Day-old commercial broiler chicks (273) were reared together until 7 days of age and on 7th day, and individually weighed, and distributed randomly into 7 groups of 3 replicates with 13 chicks each. Birds in the control group were fed diets without additives (T1). The other 6 treatment groups were fed the basal diet supplemented with 0.5% dandelion leaves (T2), 1% fenugreek seeds (T3), combination of 0.5% dandelion leaves and 1% fenugreek seeds (T4), enzyme treated dandelion leaves 0.5% (T5), enzyme treated fenugreek seeds 1% (T6), and combination of enzyme treated dandelion leaves (0.5%) and (1%) fenugreek seeds (T7). The results revealed a significant improvement in the live body weight of broiler chicken fed diets supplemented with dandelion leaves and fenugreek seeds with or without enzyme treatment (T5, T6 and T7) when compared with the control group. A significant improvement in the live body weight and body weight gain was obtained in the said groups from 3 to 6 weeks of age. Highest live body weight was observed in the group fed combination of enzyme treated dandelion leaves and fenugreek seeds (T7) followed by 1892.62gÂ±5.11 in enzyme treated dandelion group (T6). Among the groups fed dandelion leaves and fenugreek seeds without enzyme, highest body weight was achieved in the group fed 1% combination of dandelion leaves and fenugreek seeds in the diet (T4), followed by the group fed fenugreek alone (T3). Fenugreek seeds showed better results in terms of growth of birds than dandelion leaves. Highest cumulative feed consumption was recorded in all the groups in which 1% fenugreek seeds were supplemented when compared with the control group. However, a nonsignificant effect was observed in the dandelion groups compared to control in terms of cumulative feed consumption. The feed conversion ratio (FCR) was significantly improved in the birds fed diets containing either raw or enzyme treated dandelion leaves and fenugreek seeds, alone or in combination, when compared with the control group. Among the different treatment groups, best FCR was observed in the group fed combination of enzyme treated dandelion leaves and fenugreek seeds (T7), followed by enzyme treated dandelion group. The mean values of serum glucose and cholesterol significantly reduced among different treatment groups compared to control, the highest reduction being observed in the groups fed combination of dandelion leaves and fenugreek seeds with or without enzyme addition. Further, the in vitro study revealed that both the dandelion leaves and fenugreek seeds have antibacterial properties with zone of inhibition as 2 mm from dandelion leaves and 2.1 mm from fenugreek seeds for the concentration of 0.5 mg/ml and 0.05 mg/ml of extract against Escherichia coli on the Mueller Hinton Agar, respectively.